Computational Physics: Challenges of University Education - Franyelit Suárez-Carreño; Luis Rosales Romero; Jose De La Paz-Ramos (Migration Letters, 2023)
This paper proposes an analysis of physics teaching in introductory university-level courses using programming techniques and computational tools. Little needs to be studied, such as the difficulties in learning computing to solve physics problems in a science classroom or how to help students overcome these challenges. This paper explores these challenges from the perspective of students and faculty in a physics classroom with a computer-integrated curriculum. The experience was put into practice in two classrooms taking advantage of the experience of the two teachers as researchers and with extensive programming knowledge. The results are mainly based on surveys to focus on the perspectives of students and teachers. Among other results, it is concluded that learning physics is more realistic for some students familiar with programming and software management. In some cases, it can generate frustration and aversion to physics in students who have yet to gain experience in software management.